Lepidiolamprologus kamambae, a new species of cichlid fish (Teleostei: Cichlidae) from Lake Tanganyika - Kullander, Sven O.; Karlsson, Magnus; Karlsson, Mikael (Zootaxa, 2012)
Lepidiolamprologus kamambae is described from the Kamamba Island off the southeastern coast of Lake Tanganyika. Itis similar to L. elongatus, L. kendalli, and L. mimicus in the presence of three horizontal rows of dark blotches along thesides. It differs from those species in the presence of a distinct suborbital stripe across the cheek. It is further distinguishedfrom L. elongatus and L. mimicus by the presence of a marbled pattern on the top of the head, and narrower interorbitalwidth (4.9–5.9% of SL vs. 6.0–7.0%). It is distinguished from L. kendalli by a shorter last dorsal-fin spine (11.2–13.3%of SL vs. 13.3–15.1 %) and presence of distinct dark blotches on the side instead of contiguous blotches forming stripesseparated by light interspaces. Lepidiolamprologus profundicola is unique in the genus having the cheeks covered withsmall scales. Scales are absent from the cheek in L. kamambae, and in the other species scales are either absent or veryfew and deeply embedded. Lepidiolamprologus nkambae was diagnosed from L. kendalli by the absence of scales on thecheek. The presence of scales in L. kendalli is variable, however, and L. nkambae is tentatively synonymized with L. kendalli for want of other diagnostic characters.